ROE as A Moderating Influence of ESG, Green Innovation and Carbon Emission Disclosure on Firm Value - Indrawan, Andri; Sophan Himawan, Irfan; Eriswanto, Elan; Amelia Rahmadini, Salma (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
This study aims to evaluate the impact of Environmental, Social, and Governance (ESG), Green Innovation, and Carbon Emission Disclosure on Firm Value, with Return on Equity (ROE) acting as a moderating variable.In the context of a business environment increasingly emphasizing sustainability and complexity, this study uses secondary data in the form of financial statements from mining sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2022.The independent variables in this study include ESG, environmentally friendly innovation, and carbon emission disclosure, while the company value serves as the dependent variable and ROE as the moderator.To analyze the direct relationship and moderation effects, multiple regression and Moderated Regression Analysis (MRA) methods were used.The research findings indicate that the three independent variables have a positive and significant impact on the company's value.In addition, ROE has been proven to strengthen the influence of ESG, green innovation, and emission disclosure on company value.Companies with higher ROE tend to have a stronger correlation between sustainability practices and increased company value